2015
DOI: 10.4314/jae.v19i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Growth Enhancement Support Scheme among Rice Farmers in Anambra State, Nigeria

Abstract: The study assessed growth enhancement support (GES) (4.7% and 32.4% in 2012 and 2013, respectively) (M= 2.45), poor awareness (M= 2.55), and poor mobile phone possession and usage (M= 2.76). It was recommended that more awareness and adequate training be given to farmers for them to participate actively and for other farmers to join the scheme. Also there is need for the scheme to be passed into law to become policy for continuity and sustainability. . The Scheme made great changes in food productivity (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 0 publications
1
22
0
1
Order By: Relevance
“…(Anjum, 2015;Asenso-Okyere & Mekonnen, 2012;David-West, 2010;Jato & Terna, 2015;Manda & Chapota, 2015;Nwalieji, 2015).…”
Section: Use Of Foreign Language and Inappropriate Cultural Context Cunclassified
See 3 more Smart Citations
“…(Anjum, 2015;Asenso-Okyere & Mekonnen, 2012;David-West, 2010;Jato & Terna, 2015;Manda & Chapota, 2015;Nwalieji, 2015).…”
Section: Use Of Foreign Language and Inappropriate Cultural Context Cunclassified
“…The reviewed research literature explicitly highlights the illiteracy of SSFs (Anjum, 2015;McCole et al, 2014;Nwalieji, 2015), low education and training as new technology emerges (Anjum, 2015;Schalkwyk et al, 2017), the failure of SSFs to follow directives from experts (Ifeoma & Mthitwa, 2015), inadequate or short training duration (Amadu et al, 2015;Tisselli, 2015), and the existing digital divide (individuals, households, business, and geographical areas) at different socio-economic levels about opportunities to access ICT. This calls for enhanced education and training on ICT-related tools including mobile phones to add skills and knowledge to SSFs that will ultimately improve the use of technology to support the farming decision-making process and might increase the farm yield.…”
Section: Theftmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the extent to which the GESS initiative has contributed to farmers' agricultural production in rural Nigeria remains contested (Nwalieji et al, 2015;Tiri et al, 2014). Yet, Adenegan et al (2018) recently added some nuances to the debate as they suggested that the GESS initiative impacted on the farm income of cassava and maize farmers in Oyo State, Nigeria; indicating that productivity-enhancing agricultural innovations can contribute to raising the income of farming households, thereby improving poverty alleviation and food security in developing countries.…”
Section: Introductionmentioning
confidence: 99%